Pochod živých. Odpověď na pochody smrti? - Zbyněk Tarant (AntropoWebzin)
The so-called „March of the Living“ program is the largest holocaust memorial event in the world. The whole 10 to 14 days-long program, attended by thousands of participants, consists of visits to former Nazi extermination camps in Treblinka and Majdanek and culminates by 3km memorial march from Auschwitz to Birkenau. After a powerful ceremony in Birkenau, the participants continue their journey to Israel, where they take part in Yom ha-Zikaron remeberance (IDF fallen soldiers memorial day) and Yom ha-Atzma'ut (Israeli independence day) celebrations. The whole event, organized by the International March of the Living organization, founded in 1998 by Avraham Hirschson became an important event in the lives of Jewish youth to the extent, that it is sometimes compared to the famous „Bar Mitzvah“ ritual of transcendance. On the other hand, the program became subject of criticism and conthroversy. Author of this article took part in the event in 2008 and 2010. The following lines contain author's observations, interpretation of the relevant rituals and simple retrieval of contemporary Jewish discussion about the nature and meaning of the event itself. Could the March of the Living be „the“ adequate response to the Death-Marches?